(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This study aims to discuss the possible effects of the COVID-19 pandemic on the lives of Brazilian women living in poverty, and the emergency measures adopted by the government to mitigate these effects. The research is exploratory qualitative of bibliographic and documentary research, through analysis of the reports of the United Nations Organization and its international agencies, as well as the emergency measures adopted by the federal powers. Women in poverty are more vulnerable to the direct and indirect effects of the disease, because of the social inequalities that affect them in such a way that they are unable to comply with sanitary measures. The importance of emergency measures lies in the essential principle of social empowerment and economic autonomy, so that these women can maintain their life and health capacities. Keywords: Human development; Social differences; Pandemic effects; women and vulnerability.